2006
DOI: 10.1016/s1808-8694(15)31016-8
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and ultrastructural study after partial inferior turbinectomy

Abstract: Surgery proved to be effective on a short-term but not on a long-term basis, and histological recovery did not accompany improvement of clinical signs and symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 6 publications
0
8
0
2
Order By: Relevance
“…(Lindemann et al, 2005b) The assumption is made that post-operative mucosa behaves similarly to non-operated mucosa since total recovery of the morphologic and functional components of the regenerated epithelium is likely. (Bandos et al, 2006;Hegazy et al, 2014) The flow disturbance caused by small vortices and sideways motions within the narrow nasal valve probably already allows for intensive air-mucosa contact regardless of the absence of the head of the inferior turbinate. (Keck et al, 2001;Lindemann et al, 2002a;Na et al, 2012;Wiesmiller et al, 2007) Small differences in temperature associated with the extent of turbinate resection began to manifest around the level of the midinferior turbinate.…”
Section: Discussionmentioning
confidence: 99%
“…(Lindemann et al, 2005b) The assumption is made that post-operative mucosa behaves similarly to non-operated mucosa since total recovery of the morphologic and functional components of the regenerated epithelium is likely. (Bandos et al, 2006;Hegazy et al, 2014) The flow disturbance caused by small vortices and sideways motions within the narrow nasal valve probably already allows for intensive air-mucosa contact regardless of the absence of the head of the inferior turbinate. (Keck et al, 2001;Lindemann et al, 2002a;Na et al, 2012;Wiesmiller et al, 2007) Small differences in temperature associated with the extent of turbinate resection began to manifest around the level of the midinferior turbinate.…”
Section: Discussionmentioning
confidence: 99%
“…7 Study by Bandos et al, stated that improvement in relief of nasal obstruction was seen in 90% cases undergone by septoplasty with partial inferior turbinectomy. 8 Study by Stolzel et al, stated that septoplasty with turbinectomy is an ideal treatment choice in relief of nasal obstruction symptoms than septoplasty alone. 9 Study by Elwany et al, Bambirra et al reassessed their study cases one year after PIT, obtained 82.72% and 75% improvement in nasal obstruction respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies analyses image data from CT images of patients presenting clinical problems related to the nasal cavity 5,8,10,13,14 . The literature also reports a robust association between nasal concha hypertrophy and the side to which the nasal septum is diverted 1,4,11,13,14 . In the present research, we found statistically significant results for a left CB and NSD to the right side, strengthening the findings reported in various studies on nasal cavity alterations.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, chronic nasal obstruction can affect facial and whole skeletal development, resulting in an undeveloped maxilla, abnormal tooth positioning, lips that do not seal properly and induce functional changes in process as chewing, swallowing, suction and speech [10][11][12] . The symptoms and skeletal variations due to NSD and CB are applicable and useful in the forensic context.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation